Corruption, Ideology, and Populism The Rise of Valence Political Campaigning - Curini, Luigi (Springer International Publishing, 2018)
This book investigates the ideological conditions inducing political actors to highlight corruption issues through valence campaigns. Using case studies and comparative analyses of party programmes, legislatives speeches and social media data, the author demonstrates that the more parties and/or candidates present a similar policy programme, the more they rely on valence campaigns. In other words, as the ideologies of parties have become increasingly similar over recent decades, the content of political competition has substantially shifted from policy to non-policy factors, such as corruption issues. These dynamics, and the ideological considerations underpinning them, also provide a novel perspective on recent phenomena in contemporary democracies, such as the growth of negative campaigning, as well as populist strategies based on anti-elite rhetoric. The book will appeal to students and scholars interested in political corruption, valence politics, and electoral campaigning. .